Analysis of coherence areas between conjugate stations affected by the South Atlantic Magnetic Anomaly - Camacho Linares, Edwin; Benyosef, Luiz; Mendes, Odim; Oliveira Domingues, Margarete (Instituto de Geociências /Universidade Federal do Rio Grande do Sul, 2024)
The South Atlantic Magnetic Anomaly (SAMA) is a region in the South Atlantic Ocean where the Earth's magnetic field is significantly weaker than in other parts of the world. This anomaly has been of interest to scientists and researchers studying the Earth's magnetic field. The SAMA can affect navigation systems and satellite operations, and it is an important area of study for understanding the dynamics of the Earth's magnetic field. This paper investigates the signal characteristics of conjugate stations influenced by the SAMA in a moderate geomagnetic storm through record analysis of geomagnetically conjugate stations interlinking both hemispheres. This study uses the horizontal magnetic components measured in the same time interval in two typical longitudes: the America-SAMA region and the Asia-Pacific one. This procedure allows us to do a comparative analysis between regions. Our procedure uses the data recorded simultaneously in four conjugate-station pairs to characterize the magnetic variability coherence domain surrounding conjugate stations. Here, we present and discuss the first maps of the SAMA region, which corresponds to the coherence area at low latitudes. Indeed, this coherence area concept refers to the edges (close-to-the-ground geometric area) around the conjugate point, where geophysical phenomena generally exhibit similar fluctuating behavior. The correlation coefficients technique was used to calculate those areas, using the H component of the geomagnetic field. Our main results indicate that the areas in the Asia-Pacific region are similar in size and shape, which characterize typical patterns. In the America-SAMA region, the coherence areas for the conjugate stations are not similar in shape and size. These differences between coherence areas could be due to the region's unique characteristics, i.e. it presents an enhanced ionospheric conductivity. Additionally, geomagnetic stations inside a large area of South America, involving the Santa Maria region, will present, in principle, ...